Deciphering the generation of heterogeneity in esophageal squamous cell carcinoma metastasis via single-cell multiomics analysis - Kaiwen Sheng; Jun Chen; Ruitang Xu; Haoqiang Sun; Ran Liu; Yongjie Wang; Wenwen Xu; Jiao Guo; Miao Zhang; Shuai Liu; Juan Lei; Yawen Sun; et al. (Journal of Translational Medicine)
Abstract Background Chromatin accessibility plays a crucial role in mediating transcriptional dysregulation and heterogeneity in Esophageal Squamous Cell Carcinoma (ESCC). Examining the chromatin accessibility of ESCC at single-cell level is imperative to understand how it activates oncogenes and contributes to the onset and metastasis of ESCC. Methods We performed single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) on cancerous and adjacent noncancerous tissues from four ESCC patients who were pathological staged as T1a, T2b, T3b, or T4a, to investigate whether regulatory elements are pivotal in instigating cellular heterogeneity during ESCC metastasis. In conjunction, we integrated these data with 55 scRNA-seq datasets, ChIP-seq or CUT&Tag sequencing data, Hi-C sequencing data, bulk RNA-seq data, and bulk ATAC-seq data from ESCC cell lines to dissect the mechanisms underlying the heterogeneity of ESCC and tumor microenvironment (TME). Results Our study identified enhancer-specific activation within epithelial cells orchestrated by the three-dimensional structure of chromatin that regulates SERPINH1 transcription, and promotes the epithelial-mesenchymal transition (EMT) and metastasis of ESCC. Additionally, chromatin element activation facilitated the expression of TNFSF4 in CD8 + exhausted T cells, thereby activating Tregs. Furthermore, we observed that chromatin accessibility promoted the differentiation of tumor-associated macrophages (TAMs) and cancer associated fibroblasts (CAFs). Conclusions In summary, utilizing multiomics analyses, we have revealed chromatin accessibility maps and illuminated the intricate molecular mechanisms that underlie cellular heterogeneity during ESCC metastasis, offering valuable insights to further advance research on tumor progression and deterioration.